2019
DOI: 10.1007/s00125-019-04977-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction in diabetes: how to implement emerging guidelines

Abstract: Cognitive dysfunction, including mild cognitive impairment and dementia, is increasingly recognised as an important comorbidity and complication of diabetes that affects an individual’s well-being and diabetes management, and is associated with diabetes treatment-related complications. Recent guidelines therefore recommend screening for cognitive impairment in older individuals with diabetes. In addition, these guidelines suggest that glucose-lowering treatment should be tailored in those diagnosed with cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
117
1
30

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(150 citation statements)
references
References 34 publications
2
117
1
30
Order By: Relevance
“…Furthermore, the loss of brain volume has been described in patients with diabetes, particularly in regions of the hippocampus, thalamus, and cerebellar area 42 . Meta-analysis identified reduced resting-state brain activity in all brain regions in individuals with type 2 diabetes 43 be one of the main complications of diabetes, according to the current recommendations for good practice in the care of individuals with diabetes, it has become important to perform cognitive screening or cognitive assessment of these individuals 13,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the loss of brain volume has been described in patients with diabetes, particularly in regions of the hippocampus, thalamus, and cerebellar area 42 . Meta-analysis identified reduced resting-state brain activity in all brain regions in individuals with type 2 diabetes 43 be one of the main complications of diabetes, according to the current recommendations for good practice in the care of individuals with diabetes, it has become important to perform cognitive screening or cognitive assessment of these individuals 13,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have associated T2DM with an increased risk of developing cognitive impairment and AD [3,4,7,8,33]. The reasons underlying this increased risk have not been fully elucidated to date, therefore the prevention of cognitive comorbidities in patients with T2DM represents a great therapeutic and research challenge.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has demonstrated that in both insulin-deficiency and insulin-resistance, diabetes damages hippocampus-dependent memory, and high levels of adrenal steroid corticosterone contribute to these adverse effects; rats treated with streptozotocin have reduced levels of insulin and disablement in hippocampal-neurogenesis, synaptic plasticity, and learning [6]. Despite this strong evidence, established guidelines for the treatment of individuals with both diseases are unfortunately still lacking [7]. Recently, the cognitive dysfunction sub-study of the large CARMELINA international trial has shown that the dipeptidyl peptidase 4 inhibitor linagliptin was unable to prevent cognitive decline in 1545 subjects with T2DM and cardiorenal disease, notwithstanding its effectiveness in improving glycemic control [8].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a risk factor for MCI and dementia (Alzheimer's dementia, vascular dementia, and mixed dementia) [7][8][9]. In the Japanese population, the risk of developing Alzheimer's disease and vascular dementia is approximately twice as high in diabetic patients as it is in healthy individuals [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the Japanese population, the risk of developing Alzheimer's disease and vascular dementia is approximately twice as high in diabetic patients as it is in healthy individuals [10]. The risk factors for MCI in diabetic patients may include hypertension, obesity, presence of dyslipidemia, effects of exogenous and endogenous insulin associated with the treatment of diabetes, degree of chronic hyperglycemia, duration of diabetes, and presence of hypoglycemia [7,8,11]. Sarcopenia is a risk factor for dementia in elderly population without [12,13] or with [14] diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%